Enodthelin 1 Is Elevated in Plasma and Explants From Patients Having Uterine Leiomyomas. (September 2014) - Wallace, Kedra; Chatman, Krystal; Porter, Justin; Scott, Jeremy; Johnson, Venessia; Moseley, Janae; LaMarca, Babbette
Objective: To determine a role for endothelin (ET) in progression of uterine fibroids. Design: An in vitro model of fibroid and myometrium cultivation. Patients: A total of 32 women undergoing hysterectomies for uterine fibroids and 11 women undergoing hysterectomies for abnormal uterine bleeding (control population). Results: Women with uterine fibroids were hypertensive and displayed significantly greater circulating ET-1 compared to control patients. Secretion of ET-1 was greater from the fibroids compared to myometrium explants. Endothelin 1 secretion was attenuated with blockade of the angiotensin II type 1 or endothelinA receptors. Hypoxia stimulated ET-1 secretion from both myometrium and fibroid explants. Preproendothelin messenger RNA expression increased with hypoxia from fibroid explants compared to normoxic controls. Conclusions: These data support the hypothesis that uterine fibroids are associated with hypertension and increased ET-1, which is exacerbated with hypoxia. These data suggest a possible link between mechanisms of blood pressure regulation and development of uterine leiomyoma.